Wakaf Produktif Perspektif Jasser Auda - Mohammad Iqbal; Andaryuni, Lilik (Bulletin of Community Engagement, 2024)
Waqf is a unique concept in Islam that has significantly impacted the development and support of economic development in Indonesia. One of the characteristics of waqf is that the assets given cannot be sold, and the benefits of waqf must be used for the public good. In addition, waqf also supports economic development. In an example of its application, waqf land can be used for agriculture or business ventures, thus generating income that can be used to help the community in various ways. This is an example of the application of productive waqf. Productive waqf is an important part of the economic development of society. In the application of Maqasid Sharia principles, productive waqf is an effort to preserve wealth or Hifdz Al-Mal. Basically, productive waqf is not only about preserving existing assets, but also maximizing their growth potential. According to Jasser Auda, Hifdz Al-Mal is not only defined as an effort to protect property from other people's interference, but holistically, namely as a person's right to obtain property in a halal manner. In a broad sense, the right in this case is related to giving someone the authority to open employment opportunities for others.